Large-scale study of the NGC 1399 globular cluster system in Fornax - Bassino, Lilia Patricia (2006)
We present a Washington C and Kron-Cousins R photometric study of the globular cluster system of NGC 1399, the central galaxy of the Fornax cluster. A large areal coverage of 1 square degree around NGC 1399 is achieved with three adjoining fields of the MOSAIC II Imager at the CTIO 4-m telescope, Working on such a large field, we can perform the first indicative determination of the total size of the NGC 1399 globular cluster system. The estimated angular extent, measured from the NGC 1399 centre and up to a limiting radius where the areal density of blue globular clusters falls to 30 per cent of the background level, is 45 ± 5 arcmin, which corresponds to 220-275 kpc at the Fornax distance. The bimodal colour distribution of this globular cluster system, as well as the different radial distribution of blue and red clusters, up to these large distances from the parent galaxy, are confirmed. The azimuthal globular cluster distribution exhibits asymmetries that might be understood in terms of tidal stripping of globulars from NGC 1387, a nearby galaxy. The good agreement between the areal density profile of blue clusters and a projected dark-matter NFW density profile is emphasized. © ESO 2006.